Level Up: An Indonesian Best Practice Of Building Public Servants’ Performance - Basalamah, Muhammad Syafii A. (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
Despite being encircled by many poverty regencies, some areas can escape the vicious circle. Their government agency's quality as the accelerators comes up as one fundamental driver. Thus, this study explores this issue by investigating the effect of competence and compensation on work motivation and employee performance in Wajo Regency, South Sulawesi, Indonesia. 196 public servants respond to the statistical data analysis of the variance-based structural equation model (SEM). The results confirm that competence and compensation must be adequately considered to improve employee performance. Public agencies failing to accommodate these two meridians may suffer significant drawbacks in public and economic returns.